Дослідження методів монетизації для iOS додатків - Овчинникова, А. М. (ХНУРЕ, 2024)
The purpose of this research is a systematic study of various monetization methods for iOS applications to determine their effectiveness and suitability for specific types of applications. The work aims to identify the key features of each method and provide recommendations to developers on choosing an optimal monetization strategy.
Keywords: додатки для iOS; стратегії монетизації